Theme Portrayal through Protagonist in Arthur Golden’s Memoirs of a Geisha - Christiawan, Adri; Bumi, Gentara Alam (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: This study concerned on the analysis of theme viewed from the portrayal of the main character in Arthur Golden’s Memoirs of a Geisha. This study used library research as the methodology and obtained the primary data from the novel, while the supporting data obtained from books and internet sources. The result showed the theme in Memoirs of a Geisha was about achieving a goal, to achieve one’s goal, one has to struggle. This was portrayed in 4 characteristics of the main character, Sayuri, who was strong-willed, brave, persistent, and resourceful girl. These characteristic was drawn in Sayuri’s attempt in getting close to a man who was giving her a new purpose in her life. Through some difficulties, Sayuri finally succeed in achieving her goal and spent her life with the man she loved.